Dendritic Cell Vaccination of Glioblastoma: Road to Success or Dead End - Datsi, Angeliki; Sorg, Rüdiger V. (Frontiers in Immunology, 2021)
Glioblastoma (GBM) is the most frequent and aggressive malignant primary brain tumor and remains a therapeutic challenge: Even after multimodal therapy, median survival of patients is only 15 months. Dendritic cell vaccination (DCV) is an active immunotherapy that aims at inducing an anti-tumoral immune response. Numerous DCV trials have been performed, vaccinating hundreds of GBM patients and confirming feasibility and safety. Many of these studies reported induction of an anti-tumoral immune response and indicated improved survival after DCV. However, two controlled randomized trials failed to detect a survival benefit. This raises the question, whether the promising concept of DCV may not hold true or whether we are not yet realizing the full potential of this therapeutic approach. Here we discuss the results of recent vaccination trials, relevant parameters of the vaccines themselves and of their application as well as possible synergies between DCV and other therapeutic approaches targeting the immunosuppressive microenvironment of glioblastoma.